THE ARTIFICIAL INTELLIGENCE REVOLUTION IN PERSONALIZED EDUCATION: ETHICAL, PRACTICAL, AND REGULATORY CHALLENGES - de Abreu, Felipe Menezes; Quaresma, Elias Ramos; Silva, Emerson Leandro da Silva; Santos, Glaucia Nunes de Lima; das Chagas, Maria Joselia Mendes; da Silva, Paulo Adriano Maciel; de Jesus, Paulo Cristiano Abreu (Seven Editora, 2026)
This article analyzes the impact of Artificial Intelligence (AI), specifically Generative AI and Intelligent Tutoring Systems, on the personalization of basic and higher education. Through a bibliographic and documentary review of sources published between 2021 and 2025, it investigates how adaptive tools can mitigate learning gaps. Concurrently, it discusses the emerging regulatory landscape, with emphasis on Bill No. 2,338/2023 (Brazil) and the EU AI Act (European Union), addressing risks of algorithmic bias, data privacy, and the reconfiguration of the teaching role.DOI: https://doi.org/10.56238/sevened2026.001-016